PROJECT BASED LEARNING (PBL): THEORIES AND BEST PRACTICES IN ENGLISH PEDAGOGY - Riswanto, Riswanto (Corolla International Conference, 2022)
ABSTRACT Project-based learning is a type of instruction that can be used at all educational levels. The facilitator in this system is the teacher. The goals of project-based learning are to help students learn how to solve issues, enhance their critical thinking skills, and teach them problem-solving principles. The students collaborate in groups to address actual issues as they learn about the idea and refine their critical thinking. By learning from what they observe in their surroundings, students who participate in project-based learning are supposed to become more creative and active. It is possible to make the serial correlations that are thought to be necessary for a project-based learning approach to improve significantly. The development of students' independence and organizational abilities must be prioritized, with special attention paid to guaranteeing effective and beneficial use of electronic information resources. Teachers need ongoing assistance through opportunities for cooperation and professional development. Keywords : Project-Based Learning, Education